Cover crop planting practices determine their performance in the U.S. Corn Belt. (13th February 2023) - Koehler‐Cole, Katja; Elmore, Roger W.; Blanco‐Canqui, Humberto; Francis, Charles A.; Shapiro, Charles A.; Proctor, Christopher A.; Ruis, Sabrina J.; Irmak, Suat; Heeren, Derek M.
Abstract: Cover crop growing periods in the western U.S. Corn Belt could be extended by planting earlier. We evaluated both pre‐harvest broadcast interseeding and post‐harvest drilling of the following cover crops: (a) cereal rye ( Secale cereale L.) [RYE]; (b) a mix of rye + legumes + brassicas [MIX1], (c) a mix of rye + oat [ Avena sativa L.] + legumes + brassicas (MIX2), (d) legumes [LEGU]) and (e) a no cover crop control. These were tested in continuous corn ( Zea mays L.) [corn–corn] and soybean [ Glycine max (L.) Merr.]–corn systems [soybean–corn] at three sites in Nebraska for their effect on cover crop productivity, soil nutrients, and subsequent corn performance. At the sites with wet fall weather, pre‐harvest broadcasting increased cover crop biomass by 90%, to 1.29 Mg ha −1 for RYE and 0.87 Mg ha −1 for MIX1 in soybean–corn, and to 0.56 Mg ha −1 and 0.39 Mg ha −1 in corn–corn, respectively. At the drier site, post‐harvest drilling increased biomass of RYE and MIX1 by 95% to 0.80 Mg ha −1 in soybean–corn. Biomass N uptake was highest in pre‐harvest RYE and MIX1 at two sites in soybean–corn (35 kg ha −1 ). RYE and sometimes mixes reduced soil N, but effects on P, K, and soil organic C were inconsistent. In soybean–corn, corn yields decreased by 4% after RYE, and in corn–corn, by 4% after pre‐harvest cover crops. Site‐specific selection of cover crops and planting practices can increase their performance while minimizing impacts on corn. Core Ideas: Pre‐harvest broadcast cover crops had greatest productivity in sites with wetter fall weather. Cereal rye was the most productive cover crop, followed by mixes. Cereal rye and sometimes mixes lowered soil N. Cover crop effects on soil P, soil K, and soil C were small. Cover crops reduced corn yields by 4% or less.